HEPA Promotion in the Environment of Academic Scientists - Preliminary Research - Cynarski Wojciech J.; Grzywacz Renata; Kubala Krzysztof; Kunysz-Rozborska Magdalena; Podolski Adam; Pawelec Przemysław (Sciendo, 2016)
The theoretical framework for this research is the sociology of leisure and the sociology of health. Because sedentary behaviour (of employees) is a relevant new research area with important health risks, we decided to focus our attention on this subject. Moreover, sedentary behaviour in the workplace seems to be an important topic for the future.